BULUGH DAN BIOPSYCHOLOGICAL RUSHD: KRITIK NORMATIF ATAS USIA MINIMAL NIKAH PERSPEKTIF TURATS DAN NEUROSAINS - Ahmad Syihab Ramadhan (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study critically examines the minimum marriage age standards in classical fiqh through an epistemological integration of the Islamic turats specifically the concept of rushd in Maqasid al-Shari’ah and neuroscientific findings on the maturation of the prefrontal cortex (PFC). A normative-comparative approach based on library research was employed, drawing on primary sources such as classical fiqh texts (al-Umm, Bidayat al-Mujtahid, al-Mughni), Indonesian legislation, and reputable neuroscience journals. The study found that rushd al-akl in the Islamic tradition is epistemically compatible with biopsychological maturity in neuroscience. Data on marriage dispensations in Indonesia from 2019 to 2023 show an approval rate of 81–87%, indicating that judges still rely solely on bulugh as a consideration. The proposed synthesis of rushd and biopsychological concepts strengthens the normative foundation for reforming the marriage age by integrating the Maqasid of hifz al-nasl and hifz al-'aql with neurobiological evidence.